The Performance Analysis of The 3D Printer Corexy FDM Type With Area X=200 Y=200 Z=200 mm - Faris Dwi Mulyanto; Yuris Setyoadi; Rifki Hermana (Jurnal Teknik Mesin Mechanical Xplore, 2022)
A 3D printer is the result of the development of automated machining technology, which progresses from the creation of a design to the printing of a product with a complex shape and high precision for optimal printing results. The 3D printer design process begins with the creation of a design to determine the machine's dimensions, followed by the determination of specifications for the required motors, the design of electrical wiring to select the specifications for a controller, and finally, the testing of the tools when 3D printing. The accuracy of 3D corexy printers and 3D Cartesian printers are compared experimentally in this study. The printing process using a 3D printer produced two values that exceeded the tolerance limit, one in each dimension's length and width, according to the results of ten tests. The printing process results in a 3D Printer Cartesian exceeding the tolerance limit by four values: one for the length dimension, two for the width dimension, and one for the height or depth dimension. The 3D Printer Corexy is consequently more precise than the 3D Printer Cartesian because it fails less frequently.